2019
DOI: 10.3221/igf-esis.48.36
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of TIG welded joints of Unalloyed Commercially Pure Titanium Gr-2 for Weld Process Parameters

Abstract: Titanium and titanium alloys can be welded by gas tungsten arc, gas metal arc, plasma arc and electron beam welding processes. Titanium material is a reactive metal and is sensitive to embrittlement by oxygen, nitrogen, and hydrogen gas at elevated temperatures. Consequently, the metal must be protected from atmospheric contamination. This can be provided by shielding the metal with welding grade inert gas. The present work describes the application of TIG arc welding to titanium and investigated the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Gurevich et al [ 27 ] found that the increase in the penetration depth in TIG welding could be attributed to the application of the salts of alkali metals. Patil et al [ 28 ] studied the effect of gas flow rate, weld gap and weld current on the mechanical properties of CP Grade 2 titanium TIG-welded joints. A significant grain coarsening was found in the FZ consisting of an α phase bounded by a β phase.…”
Section: Introductionmentioning
confidence: 99%
“…Gurevich et al [ 27 ] found that the increase in the penetration depth in TIG welding could be attributed to the application of the salts of alkali metals. Patil et al [ 28 ] studied the effect of gas flow rate, weld gap and weld current on the mechanical properties of CP Grade 2 titanium TIG-welded joints. A significant grain coarsening was found in the FZ consisting of an α phase bounded by a β phase.…”
Section: Introductionmentioning
confidence: 99%